Violence against women in armed conflict - Gintere, Sarma (Riga Graduate School of Law, 2018)
This thesis explores the mechanisms available to the United Nations Security Council to ensure implementation of its resolutions on women, peace and security; and the mechanisms available to the Committee on the Elimination of Discrimination against Women (CEDAW Committee) to ensure implementation of the Convention on the Elimination of All Forms of Discrimination against Women and its interpretations of it. These mechanisms are explored within the focus of preventing, eliminating and punishing violence against women in armed conflict. The thesis provides insight into international law norms relevant to the issue of violence against women in armed conflict and the development of the issue in international law. It highlights the work of the Security Council and the CEDAW Committee on this issue, including the interactions between both entities and explores potential for increasing synergy between them.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; United Nations Security Council; Armed conflicts; Women